2022
DOI: 10.1016/j.jmh.2022.100081
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and depression, anxiety, stress, and PTSD among Syrian refugee parents in Canada

Abstract: Introduction The high frequency of COVID-19 has had an impact on the psychological health of all countries and socioeconomic groups around the world, with refugees suffering the brunt of the burden. The aim was to assess the relationship between fear of COVID-19 and depression, anxiety, stress, and PTSD among Syrian refugee parents residing in the Greater Toronto Area. Methods A convenience sample of 274 Syrian refugee parents residing in Ontario was recruited. Fear of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
(50 reference statements)
2
9
0
Order By: Relevance
“…Studies show that low social support and a lack of knowledge about the steps that needs to be taken to lower the prevalence of stress, depression, and anxiety are related ( 28 , 37 ). For example, in the study by Sharif-Esfahani et al ( 27 ) there was a positive association between a person’s sense of belonging to Canada and stress and anxiety measures. The lower once sense of belonging to Canada, the higher levels of stress and anxiety – a situation likely to have been exacerbated by isolation and a lack of social support during the pandemic.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies show that low social support and a lack of knowledge about the steps that needs to be taken to lower the prevalence of stress, depression, and anxiety are related ( 28 , 37 ). For example, in the study by Sharif-Esfahani et al ( 27 ) there was a positive association between a person’s sense of belonging to Canada and stress and anxiety measures. The lower once sense of belonging to Canada, the higher levels of stress and anxiety – a situation likely to have been exacerbated by isolation and a lack of social support during the pandemic.…”
Section: Resultsmentioning
confidence: 96%
“…According to three studies among refugees and asylum seekers with the aim of assessing the relationship between COVID-19 related fear and stressors and mental health, it was found that depression, anxiety and stress in relation to the fear of being infected, and associated consequences, were moderate to high ( 27 , 28 , 37 ). In one of the studies, among 274 Syrian refuges in Canada ( 27 ), severe anxiety (26.8%) depression (12.2%) and stress (9,7%) were associated with the fear of contracting COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced social and physical contact has also been associated with feelings of hopelessness, suicidal thoughts, depression, PTSD, and substance abuse [16,17]. Furthermore, several studies have documented the association between COVID-19 fear and various indices of psychological distress, particularly depression, loneliness, anxiety, and PTSD [18][19][20].…”
Section: Fear Of Covid-19 Among Schoolteachersmentioning
confidence: 99%
“…Hung et al reported the overall prevalence of anxiety and depression in the community as 35.1% and 20.1%, which was significantly higher in younger people [9]. In addition, a study on psychological distress in the general population of Canada found that people aged 18-30 or over 60 had the highest scores on the Covid-19 Peritraumatic Distress Index [10]. Several smaller-scale studies (n < 400) have also demonstrated worsening psychological symptoms in groups of young people in the USA, Italy, India, Switzerland, and China [11].…”
Section: Introductionmentioning
confidence: 99%